2022
DOI: 10.1523/jneurosci.1892-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Caution Influences Avoidance and Approach Behaviors Differently

Abstract: While conflict between incompatible goals has well-known effects on actions, in many situations the same action may produce harmful or beneficial consequences during different periods in a nonconflicting manner, e.g., crossing the street during a red or green light. To avoid harm, subjects must be cautious to inhibit the action specifically when it is punished, as in passive avoidance, but act when it is beneficial, as in active avoidance or active approach. In mice of both sexes performing a signaled action t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This increased variance could be characterized as a measure of "hesitancy" or "caution" during this reward seeking behavior. Indeed, a recent study found that mice delayed their action for a signaled reward when a new, unsignaled rule that punished the action was added 42 . However, the interpretation from that study suggested that this "caution" is not due to an anxiogenic state as it is unaffected by diazepam administration 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased variance could be characterized as a measure of "hesitancy" or "caution" during this reward seeking behavior. Indeed, a recent study found that mice delayed their action for a signaled reward when a new, unsignaled rule that punished the action was added 42 . However, the interpretation from that study suggested that this "caution" is not due to an anxiogenic state as it is unaffected by diazepam administration 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent study found that mice delayed their action for a signaled reward when a new, unsignaled rule that punished the action was added 42 . However, the interpretation from that study suggested that this “caution” is not due to an anxiogenic state as it is unaffected by diazepam administration 42 . This discrepancy is likely due to multiple different factors: apparatus (shuttle box vs. operant box), animal state (water-restricted vs. food-restricted), reward (water vs. sweetened pellet), and the probability of punishment (1.00 vs 0.13).…”
Section: Discussionmentioning
confidence: 99%
“…If the animal fails to avoid during the CS, the US is presented causing a rapid escape to the other compartment, which eliminates the US and initiates a random intertrial interval until the next trial. In AA1, mice are free to shuttle between the cage compartments during the random intertrial interval that separates CS presentations; intertrial crossings (ITCs; cyan filled bars; Figure 6B ) have no consequence ( Hormigo et al, 2021b ; Zhou et al, 2022 ). The AA2 procedure is identical to AA1 but ITCs are punished; mice must inhibit their tendency to shuttle between CS presentations during the intertrial interval (unsignaled passive avoidance).…”
Section: Resultsmentioning
confidence: 99%
“…The AA2 procedure is identical to AA1 but ITCs are punished; mice must inhibit their tendency to shuttle between CS presentations during the intertrial interval (unsignaled passive avoidance). This produces a more cautious behavioral state compared to AA1 ( Zhou et al, 2022 ). The AA3 procedure is a more challenging discrimination procedure with two different CS’s presented randomly, and ITCs are not punished.…”
Section: Resultsmentioning
confidence: 99%
“…During AA2, ITCs are punished. Consequently, avoid latencies shift longer in an apparent reflection of caution (Zhou et al, 2022). During AA3, animals learn to discriminate between two CS's, passively avoiding when AA3-CS2 is presented.…”
Section: Nac Neurons Activate During Goal-directed Avoidance Movementmentioning
confidence: 99%